Equity Crowdfunding: The Influence of Perceived Innovativeness on Campaign Success. (23rd December 2021) - Le Pendeven, Benjamin; Schwienbacher, Armin
Abstract: This paper examines the impact of perceived innovativeness on the success of equity crowdfunding campaigns. Building on the investor perspective, we hypothesize a positive impact of perceived innovativeness on the campaign outcome. Our database covers 191 campaigns launched in France on different platforms, drawing on over 2, 000 individual assessments of the perceived innovativeness of the start‐ups involved, carried out by 176 participants with diverse backgrounds. We find support for our hypothesis from the investor perspective in that highly innovative projects attract more crowd investors and, in turn, raise more capital. We contribute to the understanding of how the crowd makes investment choices.